2020
DOI: 10.1111/1744-9987.13509
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration volume by once‐weekly hemodialysis is a predictor of technique survival of combination therapy with peritoneal dialysis and hemodialysis

Abstract: Overhydration is a major cause of technique failure of peritoneal dialysis (PD). Hence, we investigated the impact of ultrafiltration (UF) volume by once‐weekly hemodialysis (HD), excess volume beyond their dry weight, on technique survival of PD and HD combination therapy (PD+HD). Forty‐six anuric PD+HD patients were divided into three groups according to baseline UF volume by HD: low‐UF ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The flexibility may enable a smooth and appropriate transition of dialysis modality, and it may be of help during disastrous situations, such as recent COVID-19 pandemic [6]. On the other hand, dialysis access-related complications [4] and peritonitis [5] were risk factors of hospitalization for PD+HD, and technique survival rate was poor in those who required high ultrafiltration volume by additional HD [7]. It is necessary to identify suitable patients and establish the optimal indication for PD+HD.…”
Section: Pd+hd Compared To Hdmentioning
confidence: 99%
“…The flexibility may enable a smooth and appropriate transition of dialysis modality, and it may be of help during disastrous situations, such as recent COVID-19 pandemic [6]. On the other hand, dialysis access-related complications [4] and peritonitis [5] were risk factors of hospitalization for PD+HD, and technique survival rate was poor in those who required high ultrafiltration volume by additional HD [7]. It is necessary to identify suitable patients and establish the optimal indication for PD+HD.…”
Section: Pd+hd Compared To Hdmentioning
confidence: 99%
“…Although many studies have shown that survival after PD is comparable to HD [4][5][6], a poor technique survival rate is a major limitation of PD. Previous studies have reported that the main causes for discontinuing PD are overhydration, peritonitis, and underdialysis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%